O Lenine Maranhense: fuzilamentos e cultura histórica no interior do Maranhão(1921). - Almeida, Giniomar Ferreira (2010)
This work is linked to the research line of Regional History Graduate Program in History of the Federal University of Paraíba, with a major in History and Historical Culture. This paper examines the historical culture of the shootings occurred within Maranhão in 1921 and the actions of a farmer called socialist and spiritualist Manoel Bernardino de Oliveira, dubbed by newspapers of the time of Lenin Maranhão. Manoel Bernardino became involved in a conflict in 1921 which culminated in the shooting, officer, four farmers and was reflected in electoral disputes at the regional and national levels, since the state's governor, Urbano Santos da Costa Araújo, was accused of ordering the shooting and was a candidate for vice-president of the Republic on the plate of Artur Bernardes, successor Epitácio Pessoa disputed elections in 1922. When the Prestes Column passed by Maranhão, in 1925, joined the Manoel Bernardino with a contingent of two hundred men. We study the collective memory as a constituent of historical culture, used the methods of oral history, with the analysis of statements made in police investigations and interviews with people in the region. The time frame was chosen as the central year of 1921 when the shootings occurred, but we present briefly the developments until 1925 when the Prestes Column through the life of Maranhão and Manoel Bernardino until his death in 1942.